Role of super‐selective embolization in lower gastrointestinal bleeding. Issue 9 (14th March 2018) - Senadeera, Sajith C.; Vun, Simon V.; Butterfield, Nicholas; Eglinton, Tim W.; Frizelle, Frank A.
Abstract : Background: Lower gastrointestinal bleeding (LGIB) is a common acute general surgical condition that is typically self‐limiting; however in refractory cases it can necessitate life‐saving intervention. When bleeding is refractory, super‐selective embolization (SSE) becomes an important management strategy. This study aims to evaluate outcomes of this procedure at our institution and identify predictors of clinical success. Methods: A retrospective analysis of patients with positive computed tomography angiograms for LGIB at a tertiary centre between December 2007 and May 2017. Results: Of 87 600 acute general surgical admissions, 2700 were for LGIB. Computed tomography angiography demonstrated active bleeding in 104 patients who then had mesenteric angiograms. SSE was performed in 77 patients of whom 66 (86%) demonstrated active bleeding. Technical success was achieved in 75 patients (97%). Clinical success was achieved in 63 patients (81%). Re‐bleeding occurred in 14 patients (19%), with four requiring surgery. One patient went forward for re‐embolization. Bowel ischaemia occurred in four patients (5.2%), with two requiring bowel resection. A 30‐day mortality following SSE was 6.5%, with one death attributable to bowel ischaemia and four deaths from medical comorbidity. Median age (years) of those who had clinical success was 78 (interquartile range (IQR) 16.4) and those who did not was 65 (IQR 20.2) ( P = 0.031). Clinical success was more common in those who had diverticular related bleeding (61.9%) compared to other pathologies (38.1%) ( P = 0.036). Conclusion: SSE was successful in a high proportion of patients in this series with low complication rates. Clinical success was higher in those who were older or with diverticular related bleeding.